Environmental assessment based on soil loss, deforestation in permanent preservation areas, and water quality applied in the Itacaiúnas Watershed, Eastern Amazon - Paulo Rógenes Monteiro Pontes; Rosane Barbosa Lopes Cavalcante; Gabriel Negreiros Salomão; José Tasso Felix Guimarães; Roberto Dall’Agnol (International Soil and Water Conservation Research)
To understand how various environmental pressures may threaten the Amazon territory, specifically its hydrographic basins, it is crucial to guide key management actions such as soil conservation, environmental preservation, and forest restoration. This paper, based on a detailed study conducted in the Itacaiúnas River Watershed (IRW) located in the Carajás mining province—one of the most significant metallogenetic provinces globally and within the Arc of Deforestation in the Amazon—proposes a new index to assess environmental threats or vulnerabilities. The index evaluates soil loss, deforestation in permanent preservation areas, and water quality—key environmental issues in watershed management. Using geoprocessing and remote sensing techniques, we applied the index across the entire catchment area and at the beginning of the drainage network (a proxy for river springs). Our findings reveal that: i) 68% of unit catchments (32% of headwaters) exhibit “High” or “Very High” soil loss vulnerability; ii) 69% of unit catchments (32% of headwaters) have more than 20% of their permanent preservation areas deforested, representing the primary threat among the three criteria to the basin; iii) Only 4.7% of unit catchments (2% of headwaters) present any chemical risk related to water consumption. The combined criteria (simple arithmetic mean of normalized values) indicate that the east-central and southern parts of the watershed have higher index values, necessitating greater attention to soil conservation. In contrast, the center-western area of the basin, characterized by conservation units and indigenous land, showed low index values but remains at risk primarily due to soil loss if environmental preservation actions are not maintained.